2021
DOI: 10.1039/d1dt00615k
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of zinc-doped Cu5Sn2Se7 and Cu5Sn2Te7

Abstract: High-performance thermoelectric materials are currently being sought after to recycle waste heat. Copper chalcogenides in general are materials of great interest because of their naturally low thermal conductivity and readily...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…It is observed that the total κ of the pristine CSS reduces from 8.18 W K –1 m –1 at RT to 4.06 W K –1 m –1 at 770 K. These values are higher than 5.3 W K –1 m –1 at RT and ∼3.3 W K –1 m –1 at 700 K but lower than 10.0 W K –1 m –1 at RT and ∼4.2 W K –1 m –1 at 750 K . After the incorporation of In 2 Te 3 , the total κ for the sample at x = 0.1 reduces from 3.9 W K –1 m –1 at RT to 1.4 W K –1 m –1 at 770 K, comparable to those of Zn-doped Cu 4 ZnSn 2 Se 7 . However, they are much higher than many of the state-of-the-art TE materials and Cu chalcogenides, which give only ∼1.0 W K –1 m –1 or less at RT. …”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…It is observed that the total κ of the pristine CSS reduces from 8.18 W K –1 m –1 at RT to 4.06 W K –1 m –1 at 770 K. These values are higher than 5.3 W K –1 m –1 at RT and ∼3.3 W K –1 m –1 at 700 K but lower than 10.0 W K –1 m –1 at RT and ∼4.2 W K –1 m –1 at 750 K . After the incorporation of In 2 Te 3 , the total κ for the sample at x = 0.1 reduces from 3.9 W K –1 m –1 at RT to 1.4 W K –1 m –1 at 770 K, comparable to those of Zn-doped Cu 4 ZnSn 2 Se 7 . However, they are much higher than many of the state-of-the-art TE materials and Cu chalcogenides, which give only ∼1.0 W K –1 m –1 or less at RT. …”
Section: Resultsmentioning
confidence: 92%
“…The compound Cu 5 Sn 2 Se 7 (CSS), which consists of affordable, non-toxic, and earth-abundant elements, has a potential for practical application in thermoelectrics if its thermoelectric (TE) performance can be improved remarkably. Although the number of cations is equal to that of anions, there is electron deficiency in CSS, leaving one hole ( p + ) in terms of the valence state of each atom: [Cu 1+ ] 5 [Sn 4+ ] 2 [Se 2– ] 7 × 1 p + , which accounts for its high carrier concentration ( n H ∼ 3.0 × 10 21 cm –3 at room temperature). Owing to its high n H , CSS has high electrical conductivity and electronic thermal conductivity ( κ e ) with the peak ZT value of only ∼0.13 at 700 K . Therefore, optimization in n H is required to improve its TE performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differently doped SnSe materials had their k values calculated from the thermal diffusivity (D), measured by the TA Instruments LASERFLASH DLF-1 system under an ultrapure argon atmosphere, the specific heat (C p ) calculated using the Dulong-Petit method, and the density (r) determined with the Archimedes method via k = DC p r. The experimental error of the thermal conductivity measurement was estimated to be 5% based on prior experience. [42][43][44] The number of data points collected for D depended on the sample stability with relation to the appearance of bubbles on the surface after the hightemperature diffusivity measurement, surface oxidation, and decomposition of material in pellet form into powder; typically we measured from room temperature to 926 K or less. 41 The selected elements Li, Na, Cu, Ag, Au, Ge, Bi, S, Cl, and Br for this study as dopants for SnSe fell in the category of low environmental impact and medium or high abundance on earth.…”
Section: Data Collection and Feature Generationmentioning
confidence: 99%
“…In contrast, the investigation of the telluride members of an extended I-II-IV-VI family is rather limited to date [11][12][13][14][15][16] despite their bandgap being more suitable for photovoltaics [17] and the tellurides preferable for applications in thermoelectrics. [18][19][20][21][22] Therefore, CZTTe (or its alloys with CZTS and CZTSe) can also be a more efficient, sustainable, and probably cheaper alternative to Si, CdTe, HgCdTe, PbS, PdSe, etc. in various applications.…”
Section: Introductionmentioning
confidence: 99%